Factors Causing Early Childhood Caries In Early Children - Willia Novita Eka Rini (Lembaga Pengembangan Kinerja Dosen, 2024)
Caries is a dental and oral disease problem whose prevalence is still quite high in Indonesia. Dental caries causes pain in the teeth, which interferes with the absorption of food, which can affect children's growth and become a serious disease that often occurs in children. Indonesian Basic Health Research in 2018 showed that 93% of young children experienced dental caries. The aim of this research is to discuss the factors that cause dental caries in early childhood. This research is descriptive research with a systematic review method. The literature search strategy uses a prism flow diagram, as well as inclusion and exclusion criteria. The databases used include Science Direct, Taylor and Francis, and Google Scholar. All 22 articles used cross-sectional research. Overall, the journal articles obtained discuss the factors that cause anal tooth caries at an early age, namely maternal knowledge, consumption of sweet foods, tooth brushing habits, maternal education, maternal behavior and formula milk.